The Determinant of Islamic Performance Ratio: Do Financing Deposit Ratio, Financing Quality, and Return on Asset Ratio Matters? - Lucky Nugroho; Erik Nugraha; Ahmad Badawi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2020)
Islamic banks have the aim of providing benefit to all humankind. Therefore, to measure the performance of Islamic banks, different indicators are needed from conventional banks. One of the indicators that can be used to measure Islamic banks' performance is the Islamic performance ratio (IPR). This study aims to determine the factors that influence IPR. By employing moderated regression analysis with the panel data of 7 Islamic commercial banks during 2012-2017, this study found that several factors are significantly influencing the performance of Islamic banks as indicated by the IPR indicator. That is the return on asset ratio (ROA) which has a positive direct effect on IPR and non-performing financing (NPF) that becomes a moderating variable for the effect of financing to deposit ratio (FDR) on IPR that weakens FDR’s effect. Although the NPF does not have a direct influence on the performance of Islamic banks, Islamic banks still have to be careful with NPF, because it can reduce the effect of FDR on the performance of Islamic banks.